Media Discourse Space Effect on the Professional Development of University Students - Guslyakova, N; Guslyakova, A (KnE Life Sciences, 2018)
The mass media of the first decades of the new millennium (the new media) are characterized not only by the paramount informing function but they are also distinguished by their ability to interact and influence the target audience in both spontaneous and dramatized modes. Simple navigation and a quick and easy access to their content stand behind the increasing popularity of the new media among younger generation. Modern new media provide the discourse space where young people, or ‘the millennials’, feel as if they are in the center of various political, social and economic events; the so-called ‘Big Brothers’ having impact on people’s life in the society. Taking into account the facts that are directly connected with the existence of the youth in the media discourse space, this article aims to track and analyze the influence of the new media on the bachelor’s and master’s students’ professional selfconcept. Our research introduces the working hypothesis that today’s media discourse space affects both directly and indirectly on university students, no matter what their future specialization is. Our students’ survey was conducted in three Russian higher education institutions: Institute of philology and foreign languages, Moscow Pedagogical State University (MPSU, Moscow); Faculty of Science and Technology, South Ural State Humanitarian Pedagogical University (SUSHPU, Chelyabinsk); and Ecological faculty, Peoples’ Friendship University of Russia (RUDN University, Moscow). The survey included the responses of the junior and senior bachelor’s students as well as the first- and the second-year master’s students. Young respondents were asked to evaluate the degree of the perceived information credibility, a positive and negative impact of present-day social networks on the younger generation and on their professional future; foreign languages and cultural knowledge; the students’ ability to interact with a foreign media discourse space, reading and leaving comments about different events in the Russian and foreign new media. Therefore, we established the correlation between the various types of variables that compose the system of the media discourse space and the students’ multiple reactions to their comprehension of the new media. The key influencing factors in the course of information exchange between students’ world perception and the media world were defined. The main conclusions about the extent of the new media influence (or its absence) on bachelor’s and master’s students and their professional development were drawn in the research. Keywords: new media, media discourse space, professional development, professional self-concept, undergraduate and graduate students